Typologies in comparative vocational education : existing models and a new approach - Pilz, Matthias [Verfasser] (My University, 2016)
"The ways in which vocational education and training (VET) systems are structured vary significantly from country to country, both because different countries have different objectives for their VET systems and because VET is differently embedded within the education and labour market systems of any individual country. International research in this area makes use of a range of existing typologies to characterise and compare VET systems. However, many of these typologies have weaknesses, for example in relation to the consistency of their descriptive criteria or the extent to which the typology is able to tackle more complex VET systems. This paper therefore takes a multi-perspective approach to developing a new typology that builds on existing approaches from a range of disciplines, justifies a specific combination of these approaches, and substantially expands on them. Specifically, it combines a skill formation approach with both a stratification approach and a standardisation approach. It also explicitly acknowledges the practice of learning as a criterion. This new typology enables VET systems in a range of countries to be categorised systematically across the different levels involved, including in relation to aspects as varied as government regulation, curriculum design, and teaching practices. This will be illustrated using six countries - China, France, Germany, India, Japan and the USA - as case studies. These case studies demonstrate substantial differences but also partial convergences between these countries. The typology offers both a framework for further explanatory approaches in individual country contexts and an opportunity for international comparison of key aspects of VET systems, such as the value attached to vocational qualifications and the possible transfer of VET models from one country to another." (Authors' abstract, BIBB-Doku)
Keywords: T 1.5 International vergleichende Berufsbildungsforschung; S System beruflicher Bildung; T 2.1 Bildungstheorien; S 4.3 Steuerung; L 1.3 Curriculumentwicklung; I 2.1 Deutschland; I 2.3.4 Asien; I 2.2.1 Westeuropa; I 2.3.2 Nordamerika; Vergleichende Berufsbildungsforschung; Internationaler Vergleich; Berufsbildungssystem; Typologie; Berufsbildungstheorie; Bildungssteuerung; Curriculumentwicklung; Fallstudie; Bundesrepublik Deutschland; China; Frankreich; Indien; Japan; USA